Psychometric properties of ohip-edent b&h for conventional complete denture wearers. - Srđan D Poštić (PLoS ONE, 2023)
This study assessed psychometric properties of the Bosnian language version the Oral Health Impact Profile for Edentulous Patients (OHIP-EDENT), translated from the original English language version of and evaluated the Oral Health-related Quality of Life, in complete denture wearers before and after corrections of dentures. Specialist of dental prosthetic interviewed 117 edentulous patients before and after interventions. All patients had problems with their existing complete acrylic resin dentures. During the first visit, the patients were examined by prosthodontic specialists, who registered the status of the existing acrylic complete dentures and described interventions needed to improve denture quality. The patients were interviewed, and they completed the OHIP-EDENT questionnaire. Each patient was re-examined by a prosthodontic specialist one month after the new complete acrylic dentures had been delivered. This study's basic instrument was the Bosnian language version (B&H) OHIP-EDENT questionnaire. The questionnaire's internal consistency was first assessed by Cronbach alpha coefficient, which was 0.80, and after correcting of dentures 0.76. Significantly lower scores were found in domains of functional limitation (p = 0.019), psychological discomfort (p = 0.010), physical pain (p = 0.003), and handicap (p = 0.041) after old denture corrections, as well as significantly better quality of life (reduced OHIP-EDENT Summary scores; p = 0.027). The student's t test of the OHIP EDENT B&H general and group indexes regarding the patients' conditions after denture interventions showed significant reduction of the general index (p = 0.02) along with reductions of functional limitations (p = 0.019), pain (p = 0.003), physical disabilities (p = 0.15), psychological disability (p = 0.002), and handicap (p = 0.002). The OHIP-EDENT B&H exposed good psychometric properties.